2021
DOI: 10.1139/cjm-2020-0336
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms that participate in biochemical cycles in wetlands

Abstract: Several biochemical cycles are performed in natural wetlands (NWs) and constructed wetlands (CWs). The knowledge of the microorganisms could be used to monitor the restoration of wetlands or the performance of the wastewater treatment. Regarding bacteria, Proteobacteria phylum is the most abundant in NWs and CWs, which possesses a role in N, P, and S cycles, and in the degradation of organic matter. Other phyla are present in lower abundance. Archaea participate in methanogenesis, methane oxidation, and the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…Bacteria (Proteobacteria, Chloroflexi, Nitrospirae, etc.) and archaea participate in the chemical cycle of wetland soil ( Mellado and Vera, 2021 ). Liu et al (2022) reported that the S and N cycles were significantly affected by wetland plant composition and coverage with the participation of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria (Proteobacteria, Chloroflexi, Nitrospirae, etc.) and archaea participate in the chemical cycle of wetland soil ( Mellado and Vera, 2021 ). Liu et al (2022) reported that the S and N cycles were significantly affected by wetland plant composition and coverage with the participation of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms in FWs are also critical for maintaining the relative stability of the nitrogen cycle, and diverse microorganisms are an important player in driving nitrogen conversion and its cycling processes ( Mellado and Vera, 2021 ; Sheng et al, 2023 ). Microorganisms such as nitrogen-fixing bacteria and cyanobacteria can convert atmospheric N 2 into bioavailable forms such as ammonia and nitrate, supplying the wetland ecosystem with available nitrogen ( Bae et al, 2018 ).…”
Section: Impact Of Microbial Diversity On Functional Stability Of Fre...mentioning
confidence: 99%
“…29 Flooding or inundation is thought to be a reasonably common and important disturbance type in floodplain wetlands including those in semi-arid Australia. 11,30,31 Interestingly, Rayburg et al 31 have shown that semi-arid floodplain sites subject to an intermediate level of flood disturbance also have a greater level of diversity in soil properties than those sites subject to frequent flood disturbances.…”
Section: Taxonomic Diversitymentioning
confidence: 99%
“…8 Proteobacteria is also known to be the most abundant in natural as well as constructed wetlands. 11 Floodplain soil microbes are subject to varying wet and dry conditions. 4,9 Observational and experimental studies have been conducted to understand the association of the microbial community structure and function with varying wet and dry conditions in floodplain wetlands.…”
Section: Introductionmentioning
confidence: 99%